Field hockey steps to success - Anders, Elizabeth (Human Kinetics, 2008)
Enter the game with confidence, knowing you've mastered the essentials. Field Hockey: Steps to Success combines a comprehensive, progressive approach with in-depth instruction, illustrations, and 86 drills. Whether you are new to the sport or seeking new techniques to add to your arsenal, Field Hockey: Steps to Success-part of the popular Steps to Success Series that has sold more than 1.5 million copies-will help you improve every aspect of your game.